Correlation between cystoscopy findings and symptom severity in painful bladder syndrome - Devdatt Purushottam Palnitkar; Prakash Patankar; Suresh Patankar (MGM Journal of Medical Sciences)
Background: Painful bladder syndrome (PBS) is characterized by persistent pelvic discomfort and urinary symptoms. Cystoscopy is frequently utilized to investigate bladder abnormalities in patients with PBS, particularly those presenting with persistent hematuria, refractory symptoms, or suspected bladder pathology. Objective: We aimed to evaluate the relationship between cystoscopy findings and symptom severity in patients with PBS. Materials and Methods: The study included 22 patients who underwent cystoscopy for PBS. Indications for the procedure included persistent hematuria, unrelenting symptoms, and suspected bladder pathology. Based on visual assessment, the cystoscopic findings were classified into three categories: normal, mild, and severe. Symptom severity was evaluated using a standardized symptom score questionnaire administered before treatment. Results: Of the 22 patients, 6 had normal cystoscopy findings, 14 exhibited mild changes, and 2 demonstrated severe changes. Symptom severity scores varied across the group, with no clear correlation between the severity of symptoms and cystoscopic findings. Notably, patients with severe symptoms often had normal or only mild changes on cystoscopy. Conclusion: No significant correlation was found between symptom severity and cystoscopy findings in PBS patients. This discrepancy may stem from the subjective nature of symptom scoring, the multifactorial origins of PBS symptoms, and the potential influence of functional disorders. Further research is warranted to identify additional factors influencing symptom severity in PBS.